Safinamide protects against amyloid β (Aβ)-induced oxidative stress and cellular senescence in M17 neuronal cells. Issue 1 (1st January 2022) - Gu, Xunhu; Zhang, Ge; Qin, Zhengfang; Yin, Min; Chen, Weiping; Zhang, Yangbo; Liu, Xu
ABSTRACT: Alzheimer's disease (AD) is a neurodegenerative disorder that is pathologically related to oxidative stress and cellular senescence. Safinamide is one of the clinically prescribed monoamine oxidase B (MAOB) inhibitors. It has been reported to possess therapeutic potential in neurological disorders. However, the therapeutic potential of safinamide in AD is still under investigation. In this study, we explored the effect of safinamide in amyloid (Aβ)1–42 oligomers-stimulated M17 neuronal cells. We established the in vitro model with M17 cells by treating them with 1 μM Aβ1-42 oligomers with or without safinamide (100 or 200 nM). The results show that safinamide ameliorated Aβ1-42 oligomers-induced oxidative stress in M17 cells as revealed by the decreased reactive oxygen species (ROS) production and reduced glutathione (GSH) content. Safinamide treatment significantly ameliorated senescence-associated-β-galactosidase (SA-β-gal)-positive cells and telomerase activity. Further, we show that safinamide treatment resulted in decreased mRNA and protein expressions of p21 and plasminogen activator inhibitor-1 (PAI-1). Moreover, silencing of Sirtuin1 (SIRT1) abolished the effects of safinamide on the mRNA levels of p21 and PAI-1, as well as SA-β-gal-positive cells in Aβ1-42 oligomers-induced M17 cells. In conclusion, we reveal that safinamide exerted a protective function on M17 cells from Aβ1-42 oligomers induction-caused oxidative stress and cellular senescence through SIRT1 signaling. These present results provide meaningful evidence that safinamide may be medically developed for the prevention and therapy of AD.